PENGARUH LATIHAN UNDER THE BASKET SHOT TERHADAP KETERAMPILAN SHOOTING PADA PERMAINAN BOLA BASKET PUTRA SMK NEGERI 2 PEKANBARU - Decelia Monica; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem of this research is that athletes still lack mastery of the under the basketball shot technique, which can be seen when practicing or competing in doing under the basketball shots, it turns out that there are still many inaccurate shots that do not produce points. This study aims to determine the effect of under the basketball shot training on shooting skills in the men's basketball game at SMK Negeri 2 Pekanbaru. The form of this research is a pretest posttest one group design with a sample of 14 male basketball players at SMK N 2 Pekanbaru. The instrument used in this study was a 30-second shooting test norm. To test for normality using the Lilliefors test at a significant level of 0.05α.. The hypothesis proposed is that there is an effect of under the basketball shot training on shooting skills in the men's basketball game at SMK Negeri 2 Pekanbaru. Based on the analysis of the normality test of the data, the results of the pree-test resulted in Lcount of 0.1879 and Ltable of 0.227 meaning Lcount < Ltable. While the post-test data resulted in Lcount 0.1955 and Ltable of 0.227 meaning Lcount < Ltable then, the data was normally distributed. Based on statistical data analysis, there is an average pree-test of 6.28 and an average post-test of 11.42 then based on t-test analysis, the t-test value is 16.58 and ttable is 1.771, so tcount > ttable, then Ho is rejected. and Ha accepted. Thus, it can be concluded that there is an effect of under the basketball shot training on shooting skills in the men's basketball game at SMK Negeri 2 Pekanbaru.Key Words: Under The Basket Shot Practice, Shooting Skills